A worm gel-based 3D model to elucidate the paracrine interaction between multiple myeloma and mesenchymal stem cells. (January 2020) - Spelat, Renza; Ferro, Federico; Contessotto, Paolo; Warren, Nicholas J.; Marsico, Grazia; Armes, Steven P.; Pandit, Abhay
Abstract: Multiple myeloma (MM) is a malignancy of terminally-differentiated plasma cells that develops mainly inside the bone marrow (BM) microenvironment. It is well known that autocrine and paracrine signals are responsible for the progression of this disease but the precise mechanism and contributions from single cell remain largely unknown. Mesenchymal stem cells (MSC) are an important cellular component of the BM: they support MM growth by increasing its survival and chemo-resistance, but little is known about the paracrine signaling pathways. Three-dimensional (3D) models of MM-MSC paracrine interactions are much more biologically-relevant than simple 2D models and are considered essential for detailed studies of MM pathogenesis. Herein we present a novel 3D co-culture model designed to mimic the paracrine interaction between MSC and MM cells. MSC were embedded within a previously characterized thermoresponsive block copolymer worm gel that can induce stasis in human pluripotent stem cells (hPSC) and then co-cultured with MM cells. Transcriptional phenotyping of co-cultured cells indicated the dysregulation of genes that code for known disease-relevant factors, and also revealed IL-6 and IL-10 as upstream regulators. Importantly, we have identified a synergistic paracrine signaling pathway between IL-6 and IL-10 that plays a critical role in sustaining MM cell proliferation. Our findings indicate that this 3D co-culture system is a useful model to investigate the paracrine interaction between MM cells and the BM microenvironment in vitro . This approach has revealed a new mechanism that promotes the proliferation of MM cells and suggested a new therapeutic target.